Consumer Behavior in Healthcare: Foundations, Trends and Future Research Directions - Tappy, Yunita Peggy; Mandagi, Deske W. (SAFE-Network, 2025)
This study aims to examine consumer behavior in healthcare by consolidating fragmented findings, identifying dominant themes, and providing a coherent framework for future research. Through a systematic literature review, five interconnected research streams were identified: educational and behavioral interventions, system-level healthcare delivery, psychological and behavioral drivers, technology-mediated experiences, and demographic and social determinants. Based on this synthesis, four strategic directions are proposed for future research: patient-centered segmentation and behavioral profiling to tailor nursing services, experiential factors influencing patient satisfaction and loyalty; ethical and cultural dimensions of consumer expectations, especially in multicultural and aging populations, and consumer feedback and engagement in co-designing nursing services. These insights offer a roadmap for developing inclusive, responsive, and emotionally intelligent healthcare systems. The study contributes to the literature by integrating diverse perspectives into a unified structure, enabling researchers and practitioners to better understand and respond to evolving consumer needs in healthcare. Implications include the need for personalized care models, culturally sensitive frameworks, and investment in digital health tools.